Drought Stress and Strategies to cope with it in Crops - Esmaeil Gholinezhad; Reza Darvishzadeh; Abbas Abhari (فیزیولوژی محیطی گیاهی, 2022)
Drought stress affects various aspects of plant growth (vegetative growth, reproductive growth, flower formation, pollination, fertilization, and seed formation). To reduce the effects of drought stress on plants, it is important to determine the mechanisms of plant response to drought stress. In response to drought stress, plants experience morphophysiological, biochemical, cellular, and molecular changes with the ultimate result of improved root system, leaf structure, osmotic regulation, relative water content, and stomatal regulation. The phenotypic manifestations in plants facing drought stress include drought escape (early or short growing period, day length sensitivity, and tiller control), drought avoidance (developed root system, stomatal conductance, size and frequency of stomata, accumulation of abscisic acid, and cuticle thickness and waxy crust on the leaf), drought tolerance (osmotic pressure regulation, passive regulation, active regulation, proline accumulation, and displacement of sap phloem materials), and recovery (improvement). Management methods to improve drought stress tolerance include the development of tolerant cultivars, the use of external osmotic protectors such as glycine betaine and proline, spraying with plant hormones such as abscisic acid, salicylic acid (aspirin), gibberellic acid, jasmonic acid, brasino steroids, and polyamines, application of foreign substances with antioxidants such as glutathione, ascorbic acid (vitamin C), tocopherol (vitamin E), and nitric oxide, foliar application of micronutrients such as iron and zinc, spraying with trace elements such as silicon and selenium, and microbial interactions of plants such as growth-promoting bacteria and fungi. This review article is a content analysis study that was carried out by searching related articles in reliable sites (Google scholar, Web of science, PubMed, Scopus, Sid) aiming to investigate the effects, mechanisms of tolerance, research methods, important measurable traits, drought stress management, and control.